Differential Abundance of Brain Mitochondrial Proteins in Yak and Cattle: A Proteomics-Based Study - Ma, Xiaoming; Zhang, Qiang; La, Yongfu; Fu, Donghai; Jiang, Hiu; Bao, Pengjia; Wu, Xiaoyun; Chu, Min; Guo, Xian; Yan, Ping; Liang, Chunnian (Frontiers in Veterinary Science, 2021)
The plateau adaptability and stress resistance of yaks are widely known based on their capacity to survive under severe habitat conditions. However, a few studies on brain mitochondria have characterized these adaptations at the protein level. We identified and quantified the brain mitochondrial proteins using isobaric tags for relative and absolute quantification (iTRAQ) and Proteomics. Western blotting was used to verify changes in the expression of target proteins. A total of 57 differentially abundant proteins (DAPs) were identified in the yak brain tissue. Gene Ontology (GO) analysis showed molecular functions of these DAPs including downregulated oxidoreductase activity but upregulated coenzyme binding. Significantly enriched biological processes were oxidation–reduction process (downregulated) and small molecule metabolic processes (upregulated). STRING protein interaction analysis indicated a complex interaction between dehydrogenase, transaminase, and ATP synthetase families. Reactome pathway analysis highlighted that the majority of DAPs participated in aerobic metabolic pathways such as metabolism, citric acid cycle, and respiratory electron transport. Immunoblotting confirmed that changes in FKBP4 and ATPAF2 expression were consistent with the results of mass spectrometry. We performed a high-throughput screening to identify DAPs in brain mitochondria between yak and cattle, which could explain the plateau adaptability of yaks.